2015
DOI: 10.1111/apm.12429
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell homeostasis in chronic HCV‐infected patients treated with interferon and ribavirin or an interferon‐free regimen

Abstract: Direct-acting antiviral has replaced pegylated interferon-α and ribavirin-based treatment in the treatment of chronic hepatitis C virus (HCV) infection. While interferon-α is immune modulating and causes lymphopenia, interferon-free regimens seem to be well-tolerated. This study aimed to compare T-cell homeostasis before, during, and after HCV treatment with or without interferon-α in patients with chronic HCV infection. A total of 20 patients with chronic HCV infection were treated with pegylated interferon-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…The number of N T cells may take more than 2 years after viral clearance through IFN-based therapy to reach values similar to those of HC (Alanio et al, 2015). Consistently with these observations and with a previous report (Hartling et al, 2015), the alteration of T cell subset proportion was only slightly mitigated by DAA therapies and, as already observed during HIV infection (Nicoli et al, 2016), was associated with immune activation (Shen et al, 2010). However, our results confirm these data only partially, as we show higher CD8 + T cell activation in the memory, but not in the naïve, compartment while only terminally differentiated CD4 + T cells experienced the same phenomenon.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The number of N T cells may take more than 2 years after viral clearance through IFN-based therapy to reach values similar to those of HC (Alanio et al, 2015). Consistently with these observations and with a previous report (Hartling et al, 2015), the alteration of T cell subset proportion was only slightly mitigated by DAA therapies and, as already observed during HIV infection (Nicoli et al, 2016), was associated with immune activation (Shen et al, 2010). However, our results confirm these data only partially, as we show higher CD8 + T cell activation in the memory, but not in the naïve, compartment while only terminally differentiated CD4 + T cells experienced the same phenomenon.…”
Section: Discussionsupporting
confidence: 91%
“…However, our results confirm these data only partially, as we show higher CD8 + T cell activation in the memory, but not in the naïve, compartment while only terminally differentiated CD4 + T cells experienced the same phenomenon. In addition, while DAA therapies normalized activation of EMRA CD4 + T cells, the same was not observed in the CD8 + compartment, confirming previous observations on bulk T cells (Hartling et al, 2015; Najafi Fard et al, 2018). Together with data reporting that DAA treatments normalize levels of soluble inflammatory markers only partially (Hengst et al, 2016; Kostadinova et al, 2018), these pieces of evidence suggest that IFN-free therapies have only minor effects on immune activation.…”
Section: Discussionsupporting
confidence: 88%
“…42 In the current study, most patients received IFN-based therapy indeed decrease 2-year tumor recurrence rate compared with untreated group (32.1 vs. 73.3%, p < 0.001). IFN-α exerts potent antiviral activity via stimulation of IFN-stimulated genes (ISGs) and its downstream signaling pathway 43 which causes T-cell homeostasis after SVR 44 and immune modulation effect contributing to HCC reduction. The analyses of sCTLA-4 and clinical parameters confirmed that sCTLA-4 level were negatively correlated with antiviral therapy, although this did not reach statistical significance in the current study.…”
Section: Discussionmentioning
confidence: 99%